Evaluation of the probiotic, technological, safety attributes, and GABA-producing capacity of microorganisms isolated from Iranian milk kefir beverages - Moghimani, Minoo; Onyeaka, Helen; Hashemi, Mohammad; Afshari, Asma (Frontiers in Microbiology, 2024)
Introduction: Kefir beverage has beneficial microorganisms that have health-giving properties; therefore, they have a good potential to be probiotic. This study evaluated the probiotic potential, technological, and safety characteristics of Enterococcus faecalis, Lactococcus lactis, and Pichia fermentans isolated from traditional kefir beverages.Method: First, isolates were evaluated in terms of resistance to acid, alkali, bile salts, trypsin, and pepsin of the gastrointestinal tract. The auto-aggregation and co-aggregation ability of isolates were measured using spectrophotometry. Antimicrobial activities were assayed against important foodborne pathogens using the agar well diffusion method. Moreover, gamma-aminobutyric acid )GABA) production was investigated by thin-layer chromatography (TLC).Result: Among the isolates, P. fermentans had an 85% total survival rate, but its amount reached below 6 log CFU/ml which is considered non-resistant, and it showed the highest auto-aggregation (74.67%). Moreover, only L. lactis showed antimicrobial activity and had the highest co-aggregation with E. coli PTCC 1338 (54.33%) and L. monocytogenes ATCC 7644 (78%). Finally, an evaluation of the technological and safety characteristics of the strains showed that the strains produced GABA and were safe.Discussion: Although the isolates were not resistant to the gastrointestinal tract, their supernatant contained valuable natural compounds, including antioxidants, GABA, and antimicrobials, which can be used to produce functional foods and medicines. In addition, other approaches, such as increasing the initial number of strains, using foods as carriers of isolates, and encapsulating the isolates, can effectively increase the survivability of isolates in the gastrointestinal tract.